2017
DOI: 10.32607/20758251-2017-9-1-68-74
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human Pluripotent Stem Cells into Mesodermal and Ectodermal Derivatives Is Independent of the Type of Isogenic Reprogrammed Somatic Cells

Abstract: Induced pluripotent stem cells (iPSCs) have the capacity to unlimitedly proliferate and differentiate into all types of somatic cells. This capacity makes them a valuable source of cells for research and clinical use. However, the type of cells to be reprogrammed, the selection of clones, and the various genetic manipulations during reprogramming may have an impact both on the properties of iPSCs and their differentiated derivatives. To assess this influence, we used isogenic lines of iPSCs obtained by reprogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Currently, multiple strategies have been developed for spontaneous and directed differentiation of hPSCs into specialized cells from all three germ layers [98][99][100]. In the case of mesoderm, recent advances have demonstrated the opportunity to derive various types of mesenchymal cell populations from hPSCs.…”
Section: Isogenic Cellular Models Of Different Stages Of Human Develo...mentioning
confidence: 99%
“…Currently, multiple strategies have been developed for spontaneous and directed differentiation of hPSCs into specialized cells from all three germ layers [98][99][100]. In the case of mesoderm, recent advances have demonstrated the opportunity to derive various types of mesenchymal cell populations from hPSCs.…”
Section: Isogenic Cellular Models Of Different Stages Of Human Develo...mentioning
confidence: 99%
“…Differences among hPSC lines mainly include DNA methylation[9-13] and gene expression[1,8], which have functional implications for both ESC and iPSC lines[1]. Particularly, for iPSCs, the variations may be donor-dependent[14,15] or original cell type-dependent[9], while, in other studies, this relationship was not found[10,16]. Moreover, the characteristics of hPSCs may differ depending on the number of passages[17], culture medium components[18], and feeder conditions[19].…”
Section: Introductionmentioning
confidence: 99%
“…During differentiation, it is expected that stem cells lose the expression of the pluripotency-related genes OCT4 and NANOG and begin to express markers associated with differentiation, such as GATA4 and GATA6 (Miyamoto et al, 2015). An important issue regarding epigenetic markers in stem cells is that the current methods of iPSC cultivation allow the maintenance of the epigenetic profile over a long period (Philonenko et al, 2017). Such epigenetic control may be also mediated by miRNAs ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the ability to obtain embryonic bodies from iPSCs, another advantage in using iPSCs for in vitro cell differentiation is that technical manipulations, such as selection of clones or cell sorting, do not interfere with their ability to differentiate into hematopoietic tissue (Philonenko et al, 2017). Even if iPSCs require genetic manipulations (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation